INVESTIGATING REASONS FOR RESISTANCE AMONG PROJECT AND GENERAL MANAGERS IN ENTERPRISE RESOURCE PLANNING IMPLEMENTATIONS - Amer Celjo; Azra Hanić; Marietta Kazalac (Economic Review)
Enterprise Resource Planning (ERP) primary goal is to connect all organizational units together under the single data base. It is intended to speed up all the processes and track all the actions easily. To put it simply, it is the central neural system of the organization, helping management to quickly assess the state of every part of the organism and the status of all the processes within it. As such, it should be a readily available solution to all the organizations regardless of their size, for helping them in making the processes efficient. Why are there so many cases of unsuccessful ERP implementation? The main goal of our research project is to make the scientific study and identify the major reasons for resistance to ERP implementation among general and project managers in the organizations that implemented or failed to implement the system. We have undertaken an innovative study approach collecting twenty responses from two focus groups: project managers and general managers. E-mails with specific topics regarding ERP implementations were collected from 10 general managers and ERP project managers of medium size and large organizations to prepare them for the focus group discussion. A rather limited sample and the following steps were realistically projected and executed to respect the limiting time frames and deadlines of the class.